Functionalized periodic Au@MOFs nanoparticle arrays as biosensors for dual-channel detection through the complementary effect of SPR and diffraction peaks - Hang, Lifeng; Zhou, Fei; Men, Dandan; Li, Huilin; Li, Xinyang; Zhang, Honghua; Liu, Guangqiang; Cai, Weiping; Li, Cuncheng; Li, Yue (Nano research, 2017)
A facile and low-cost method to prepare periodic Au@metal-organic framework （MOF） （MIL-100（Fe）） nanoparticle arrays was developed. The arrays were fabricated in situ using monolayer colloidal crystals as templates, followed by Au deposition on substrates, and annealing. MIL-100（Fe） coatings were applied on the nanospheres using a simple solvent thermal process. The prepared periodic Au@MIL-100（Fe） nanoparticle （NP） arrays were characterized by two peaks in the visible spectra. The first peak represented the surface plasmon resonance （SPR） of the Au nanospheres, and the other peak, or the diffraction peak originated from the periodic structure in the NP array. After modification with 3-aminophenylboronic acid hemisulfate （PBA）, the Au@MIL-100（Fe） NP arrays exhibited sensitive responses to different glucose concentrations with good selectivity. These responses could be due to the strong interaction between PBA and glucose molecules. The diffraction peak was sensitive at low glucose concentrations （less than 12 mM）, whereas the SPR peak rapidly responded at high concentrations. The peaks thus demonstrated satisfactory complementary sensitivity for glucose detection in different concentration regions. These results can be used to develop a dual-channel biosensor. We also created a standard diagram, which can be used to efficiently monitor blood glucose levels. The proposed strategy can be extended to develop different dual-channel sensors using Au@MIL-100（Fe） NP arrays agents. functionalized with different recognition